2017
DOI: 10.1007/s13205-017-1014-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of vanillin flavour metabolites by precursor feeding in cell suspension cultures of Decalepis hamiltonii Wight & Arn., in shake flask culture

Abstract: The flavour rich tuberous roots of are known for its edible and medicinal use and have become endangered due to commercial over-exploitation. Besides 2-Hydroxy-4-methoxy benzaldehyde (2H4MB), other flavour metabolites in tuberous roots include vanillin, 4-Methoxy Cinnamic acid derivatives, aromatic alcohols etc. So far, there are no reports on the pathway of 2H4MB biosynthesis nor there is an organized work on biotransformation using normal and cell suspension cultures for obtaining these metabolites using pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Vanillin is known to have a principal therapeutic potential. The vanillin is known to be synthesized by ferulic acid decarboxylation; where enhanced ferulic acid level can be directed for vanillin production [ 54 ]. Therefore, these improvements in phenolic acid production are considerable proof of the potent eliciting ability of DPS.…”
Section: Discussionmentioning
confidence: 99%
“…Vanillin is known to have a principal therapeutic potential. The vanillin is known to be synthesized by ferulic acid decarboxylation; where enhanced ferulic acid level can be directed for vanillin production [ 54 ]. Therefore, these improvements in phenolic acid production are considerable proof of the potent eliciting ability of DPS.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring of biomass of the callus cultures at regular interval revealed that the growth of the suspension cultures showed some physical changes that include color and texture. During the first week to second week, the light greenish colored callus cells start changing their color to green; later by 4th week, it was friable and dark green with 200.38 ± 1.56 g/L of biomass; after 8 weeks, they become brown with 191.41 ± 1.28 g/L of biomass (Matam et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The ionisation mode was negative. The precise mass after separation and identification of metabolites was made by injection of collected fractions into the MS system (Matam et al ., 2017).…”
Section: Biochemical Characteristics Of Biscuitsmentioning
confidence: 99%
“…The plant is known for its rich natural flavour and bioactive properties, making it an important ingredient in various indigenous foods (Kamireddy et al ., 2018; Pradeep et al ., 2019). The major bioactive molecule of tuber constitutes 2‐hydroxy 4‐methoxybenzaldehyde, an isomer of vanillin (Nagarajan et al ., 2001), and successive attempts have been made by researchers to improve the flavour content of the D. hamiltonii tubers in vitro (Pradeep et al ., 2017; Koppada et al ., 2022) and ex vitro (Giridhar et al ., 2005; Pradeep et al ., 2019). Biochemical characterisation of key biosynthetic pathway steps involved in 2H4MB production (Kamireddy et al ., 2017) and proteomic and biotechnological approaches based on the identification of abundant proteins (Kamireddy et al ., 2021) and phenylpropanoid pathway genes expression (Kiran et al ., 2018) during flavour development were respectively investigated.…”
Section: Introductionmentioning
confidence: 99%